Political Bondage: Eksistensi Sumber Daya Alam dalam Mendesain Tatanan Politik Elektoral Berbiaya Tinggi di Indonesia - Setiawan, Hendy (Bestuurskunde: Journal of Governmental Studies, 2024)
The practice of political bondage (ijon) in electoral political events is a threat to democracy, which to this day is still relatively limitedly studied. This creates minimal gaps in how to view the phenomenon of high electoral political financing from the perspective of natural resource politics. So far, natural resources have always been viewed as inanimate objects. However, in the study of natural resource politics, this object is not neutral. The presence of the political bondage system which is a small part of the form of transactional politics in the informal democratic space has actually become the identity and characteristic of electoral politics in Indonesia. In the context of political bondage, the exchange of roles between patron becoming client and, vice versa, client becoming patron will continue to recur. This research uses a qualitative approach with library research methodology. Researchers collect data through secondary data, namely various relevant literature, starting from media, books, journals, news reports, formal institutional data, and other data which is sorted according to research needs. The results show that the practice of political bondage still fulfils and always colors electoral politics in Indonesia. This informal democratic practice leads to high levels of financing of electoral politics. Interestingly, the involvement of corporations in funding general elections outside of political party funds also has an impact on reciprocation for the management of natural resources. The development of transactional political practices in informal spaces will create challenges for the quality of democracy: the birth of corrupt behavior, the weakening of the government structure, dynastic-oligarchic politics, and the increase in electoral political financing. The conclusion is that the practice of political bondage will always grow in the space of informal democracy. The relationship between the public sector, elites and the private sector will always exchange roles as patron and client according to the conditions and electoral political map in the field.